English for teacher : - Spratt, Mary (Cambridge University Press, 1994)
English for the Teacher is a course which enables teachers to improve their language ability for a number of purposes--using English in the classroom, making professional contacts, reading about the teaching of English and discussions with colleagues and students. As well as providing language practice for the four skills, it also invites teachers to comment on the learning value of what they are doing and thus discuss and reflect on different ways of teaching and learning. In this way, it provides opportunities for more general professional development.